2004
DOI: 10.1128/jvi.78.2.576-584.2004
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4-Dependent Activation of Dendritic Cells by a Retrovirus

Abstract: Mouse mammary tumor virus (MMTV) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 49 publications
2
91
1
Order By: Relevance
“…This synergy can also be explained by our findings that highlight the ability of TLR3 and TLR4-activated pathways to induce, in a type I IFN-dependent manner, sensors normally absent in iDC and ensuring in this way that powerful effectors will be generated to respond combinatorially to microbial products in different cellular compartments. Another explanation supporting this hypothesis is that TLR4 can participate in the immune response to certain viruses (62)(63)(64)(65)(66)(67); the virus-induced triggering of TLR4 can mediate the transcriptional activation of certain genes encoding intracellular sensors for viruses, such as TLR7, to amplify the response to specific viral infections.…”
Section: Discussionmentioning
confidence: 93%
“…This synergy can also be explained by our findings that highlight the ability of TLR3 and TLR4-activated pathways to induce, in a type I IFN-dependent manner, sensors normally absent in iDC and ensuring in this way that powerful effectors will be generated to respond combinatorially to microbial products in different cellular compartments. Another explanation supporting this hypothesis is that TLR4 can participate in the immune response to certain viruses (62)(63)(64)(65)(66)(67); the virus-induced triggering of TLR4 can mediate the transcriptional activation of certain genes encoding intracellular sensors for viruses, such as TLR7, to amplify the response to specific viral infections.…”
Section: Discussionmentioning
confidence: 93%
“…These authors speculate that TLR4 activation by Env may have a positive effect on viral replication by directly activating B cells, allowing an initial round of viral replication or feedback of TLR4-induced cytokines, which may promote provirus transcription. A recent study has revealed that MMTV activation of TLR4 on dendritic cells enhances expression of its entry receptor, CD71 (14), which suggests that activation of TLR4 by MMTV facilitates viral entry in addition to the replication-enhancing effects described above. This report also showed that TLR2 is activated by MMTV and that TLR2 responses may contribute to these processes (14).…”
Section: Molecular Basis Of Tlr Activationmentioning
confidence: 99%
“…A recent study has revealed that MMTV activation of TLR4 on dendritic cells enhances expression of its entry receptor, CD71 (14), which suggests that activation of TLR4 by MMTV facilitates viral entry in addition to the replication-enhancing effects described above. This report also showed that TLR2 is activated by MMTV and that TLR2 responses may contribute to these processes (14).…”
Section: Molecular Basis Of Tlr Activationmentioning
confidence: 99%
“…18 Interestingly, the Tf-R (type I, CD71) has been described to be the cell entry receptor for mouse 21 and to play a determining role in the activation of dendritic cells by this retrovirus. 22 This receptor regulates iron uptake not only in reticulocytes but in most cells. 23 As shown in Figure 3d, the TSAP6À/À BMDCs express higher levels of Tf-R than their WT counterparts.…”
Section: Tsap6mentioning
confidence: 99%